Partial loss of Akap1 promotes cardiac dysfunction, gut barrier dysfunction and alterations of gut microbiota composition during aging. (14th October 2021) - D'Apice, S; Paolillo, R; Boccella, N; Coretti, L; Lama, A; Avvedimento, M; Esposito, G; Mattace Raso, G; Lembo, F; Perrino, C; ,
Abstract: Background: Mitochondrial A-kinase anchoring proteins (mitoAKAP) encoded by the Akap1 gene are crucially involved in multiple cellular processes, including cardiomyocyte survival and function. Whether mitoAKAP levels play a role in aging and gut microbiota composition is currently unknown. Purpose: The aim of this study was to highlight the complex interplay between cardiac dysfunction, gut barrier integrity, gut microbiota composition and aging in young (6-month-old, 6m) and old (24-month-old, 24m) wild type (wt) and Akap1 heterozygous mice (Akap1+/−). Methods: Cardiac function was analyzed by echocardiography in 6m and 24m wt and Akap1+/− mice. Gut microbial DNA was extracted and gut microbiota composition was analyzed by Illumina Mi-Seq analysis. Bioinformatics analysis was carried out to identify major intestinal populations. Alpha diversity within each sample was determined, and then analyzed according to genotype and age; then, inter-sample diversity was determined. For each dataset, we used UniFrac to calculate the differences between microbial communities based on phylogenetic distance between taxa sets in a phylogenetic tree. Bioinformatics analyses were performed using the analysis of similarities (ANOSIM). To evaluate the role of mitoAKAPs in intestinal permeability, we analyzed intestinal junction proteins expression levels in colon samples of all groups. Variance analysis was performed to determine significance among the groups. Results: Partial loss of Akap1 accelerated the progression of cardiac dysfunction in 24m mice, as demonstrated by a significantly lower % fractional shortening (%FS) compared to 24m wt mice (%FS, wt 6m: 60±3; Akap1−/+ 6m: 58±5; wt 24m: 49±6*; Akap1−/+ 24m: 39±12* § ; *p<0.05 vs. wt 6m; § p<0.05 vs. wt 24m). In 24m Akap1+/− mice, aging was associated to enhanced colon permeability, as shown by reduced levels of Ocludins and Tight Junction Proteins 1 mRNA expression. A principal coordinate analysis of fecal samples based on their unweighted UniFrac distances revealed that samples from Akap1+/− 24m mice cluster apart from wt 24m samples, suggesting that Akap1+/− 24m mice exhibit a different assortment of microbial communities. This observation was supported by ANOSIM R statistic that revealed significant differences in gut microbiota composition between wt and Akap1+/− 24m mice (ANOSIM R=0.475, P=0.023), We analyzed the differences in abundance of all 2, 042 Operational Taxonomic Units (OTUs) between age-matched wt and Akap1+/−. We identified 10 OTUs differently represented in wt and Akap1+/− 6m mice, while a bigger set of bacterial OTUs (19) were different between wt and Akap1+/− 24m mice. Consistent with previous results in patients with heart failure, we identified Clostridiales, Blautia producta and R. Torques among differently regulated species. Conclusion: Partial Akap1 deletion plays an important role in the progression toward HF and modulates colon permeability and gut microbiota composition during aging. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Programma STAR Grant by Federico II University and Compagnia San Paolo